Reversal of Chorea Hyperglycemia Basal Ganglia Syndrome With Glycemic Control: A Case Report - Sumanth Gundraju; Jaideep Menda; Tarun Kumar Suvvari; Anupama Kumudavalli Pindi; Prudhvi Kumar Davala; Tejinder Singh; Vimal Thomas (Clinical Medicine Insights: Case Reports)
Chorea Hyperglycemia Basal Ganglia Syndrome (CHBG) is an uncommon neurological complication arising in diabetic patients with severe, non-ketotic hyperglycemia. This case report describes a 50-year-old woman presenting with new-onset, choreiform movements in her extremities. Initial workup revealed uncontrolled diabetes (plasma glucose 410 mg/dl, HbA1c 11.2%) with negative serum ketones. Brain MRI findings supported the diagnosis, demonstrating characteristic T1 hyperintensity in the right basal ganglia. Implementation of gradual glycemic control over 48 hours led to significant improvement of her symptoms. This case emphasizes the importance of considering CHBG in the differential diagnosis of movement disorders in patients with uncontrolled diabetes. Early recognition and prompt glycemic management can lead to complete resolution of symptoms, highlighting the crucial role of maintaining proper blood sugar control in diabetic patients.